THE ROLE OF WORK DISCIPLINE, WORK MOTIVATION, AND ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION ON NURSING PERFORMANCE IN INDONESIA - Ingsih, Kusni; Yanuardani, Rini Laksmi; Suhana, Suhana (Jurnal Aplikasi Manajemen, 2021)
This study aimed to determine the effect of work discipline, work motivation, organizational commitment on job satisfaction in improving nursing performance. The research respondents were nurses in the city of Semarang. The sample used in this study was determined by a non-probability sampling method, which obtained a sample of 190 respondents. The data in this study were obtained using a questionnaire method, which was filled independently. The analysis used in this study used multiple linear regression. This study proves and concludes that work discipline, work motivation, and organizational commitment positively affect job satisfaction. work discipline and organizational commitment positively affect nursing performance. However, work motivation and job satisfaction do not affect nursing performance. The research findings can be used as management consideration to improve the nursing performance in Semarang Indonesia and other countries with similar characteristics by applying the model to increase performance. The research is an original one. The findings add a discourse concerning the effect of work discipline, work motivation, organizational commitment, and job satisfaction on performance in nursing institutions in a developing country, Indonesia. Nursing institutions can consider the model to enhance nursing performance. Researchers can widen the scope of research for future research to overcome the problem of the generalization of research findings.